CROSS-ISLAND EDUCATION GOVERNANCE CONFIGURATION: A BIBLIOMETRIC ANALYSIS OF THE RELATIONSHIPS AMONG BUREAUCRACY, DECENTRALIZATION, AND NETWORKS IN THE COORDINATION OF CENTRAL, REGIONAL, AND EDUCATIONAL INSTITUTIONS - Rudolf Kempa; Paul Arjanto; Arsyil Waritsman (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Cross-island education management requires adaptive bureaucratic relations through a decentralization mechanism, enabling the central government, regional governments, and educational units to share roles effectively based on geographical context and local needs. Therefore, this study aims to analyze the configuration of scientific knowledge regarding bureaucratic relations, decentralization, and networks in cross-government educational coordination through a bibliometric approach based on Scopus publication data. The method used is a literature review using bibliometric analysis of scientific publication data sourced from the Scopus database, with the following criteria: publications between 2021 and 2025, Subject area: social science, document type: article, publication stage: final, country: Indonesia, source type: journal, and English language. The results of the study found that (1) the topic that has been widely carried out related to cross-island education governance is about Higher Education; (2) research related to cross-island education governance has shifted towards artificial intelligence and project-based learning topics; (3) topics that have been frequently carried out related to cross-island education governance currently are topics related to Higher Education and Digital Literacy; and (4) further research topics needed to enrich studies on educational governance are on Project-Based Learning. In general, this research contributes to mapping the direction of development of studies on cross-island educational governance. It emphasizes the importance of integrating bureaucratic relations, policy decentralization, and collaborative networks to enhance coordination among the central government, regional governments, and educational units.